A Rare and Fatal Pulmonary Cryptococcosis in HIV/AIDS: Chronological Clinical Decline in a Middle-Aged Male - Ediyono, Ediyono; Wijaya, Rike Andy; Al Amin, Yoga Dian Pratama (Green Publisher Indonesia, 2025)
Cryptococcosis represents a life-threatening opportunistic fungal infection with significant mortality rates among immunocompromised individuals, particularly those with advanced HIV/AIDS. While cryptococcal meningitis dominates the literature, pulmonary involvement remains underrecognized despite its prognostic significance. This case report aims to document the clinical presentation, diagnostic challenges, and fatal outcome of pulmonary cryptococcosis caused by the rare species Cryptococcus laurentii in a severely immunosuppressed HIV-positive patient, and to emphasize the importance of early bronchoscopic investigation and antifungal therapy. We report the case of a 44-year-old Indonesian male with a history of HIV/AIDS who presented with progressive shortness of breath, persistent cough, and intermittent fever over two weeks. He was non-adherent to antiretroviral therapy (ART) and had a CD4 count of fewer than 50 cells/mm³. Chest radiography showed bilateral infiltrates, and sputum culture grew Cryptococcus laurentii. Despite the initiation of broad-spectrum antibiotics and antifungal agents, his respiratory status deteriorated rapidly. Antifungal susceptibility testing confirmed sensitivity to amphotericin B, flucytosine, and fluconazole, yet the patient developed progressive respiratory failure. He ultimately succumbed to refractory hypoxemia on day 23 of hospitalization. This case highlights the diagnostic challenge of pulmonary cryptococcosis in advanced HIV, particularly with rare non-neoformans species. A high index of suspicion and early mycological investigation, including culture and species-level identification, are critical for timely diagnosis. This report contributes to the limited literature on C. laurentii pulmonary infections in Southeast Asia and underscores the importance of adherence to ART, as well as the need for early consideration of fungal infections in severely immunosuppressed patients presenting with atypical pulmonary findings.